Incentives and Compensation in Ethiopian Football - Tadesse, Samson; Asgedom, Tesfay; Taddese, Aschenaki (Universitas Majalengka, 2023)
The Ethiopian Football Federation has faced challenges in improving the quality of football in Ethiopia due to a need for more resources and infrastructure. In Ethiopian football, incentives play an important role by providing financial support for players, attracting talented players to clubs, and motivating players to perform at their best. However, there are also some challenges associated with incentives. In this study, fourteen Ethiopian Higher League Football clubs and league committees participated. Semi-structured interview guideline was used to collect qualitative data from all fourteen football clubs. The qualitative data obtained from field notes and recorded semi-structured interviews were entered into Nvivo, version # 12, for better data management and coding of the themes and subthemes. The findings of this study revealed that incentives are an important aspect of motivating footballers to perform well and achieve success. In addition, there have been efforts to improve payment and compensation in Ethiopian soccer.